2021
DOI: 10.1108/jbim-01-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Value creation in company–NGO collaboration in corporate volunteering

Abstract: Purpose This paper aims to examine corporate volunteering as a form of social responsibility carried out by companies in relationships with non-governmental organizations (NGOs). Applying the value creation concept, the success of such relationships is based on value created between the focal company, its employees engaging in the volunteer work and the collaborating NGO actors representing the beneficiaries of the volunteer work. However, how to meaningfully engage employees and strategically manage company–N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Langan and Kumar (2019) suggest that a longer corporate donation time leads consumers to give more altruistic attributions to a firm. Specifically, long-term commitments can be perceived by the public as a firm's genuine concern to promote social welfare and thus these commitments have a positive impact on CR; by contrast, short-term activities can be perceived by the public as the corporate exploitation of socially responsible causes for profit, and this is detrimental to the establishment of a high CR (Brzustewicz et al. , 2021; Webb and Mohr, 1998).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Langan and Kumar (2019) suggest that a longer corporate donation time leads consumers to give more altruistic attributions to a firm. Specifically, long-term commitments can be perceived by the public as a firm's genuine concern to promote social welfare and thus these commitments have a positive impact on CR; by contrast, short-term activities can be perceived by the public as the corporate exploitation of socially responsible causes for profit, and this is detrimental to the establishment of a high CR (Brzustewicz et al. , 2021; Webb and Mohr, 1998).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Thus, even local voluntary activities—because of the multiplier effect—may be translated into significant changes (e.g. CR) at the macro level (Brzustewicz et al. , 2021).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Under the concept of autonomous organization and governance, nongovernmental organizations use organizational behavioral rules to establish collective behavioral norms and informal institutions to increase the initiatives of organizational members. Brzustewicz et al (2021) explored multiple incentive mechanisms, finding that environmental values, beliefs, and reputation scores are effective monitoring mechanisms for safeguarding collective behavioral norms. In contrast to the heterogeneity in the effects of external constraints on group norms, such as under reward, incentive institutions, and marketization mechanisms, Allcott (2011) and Bolsen et al (2014) found that household water and energy consumption behaviors across different groups show significant differences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, this general “triple win” approach to CSR gradually gives way to a more diversified, nuanced, and sophisticated approach to the business case, ranging from perspectives of knowledge creation (e.g., Lysova & Saduikyte, 2015), value creation (e.g., Brzustewicz et al, 2021), concrete quantitative measures (e.g., Mayer & Costa e Silva, 2017), and social capital and internal market intelligence (e.g., Glińska‐Neweś & Górka, 2020). For example, Bartsch (2012) discusses how organizations can link social engagement and inner management growth and profile the opportunities for knowledge growth.…”
Section: From the Perspective Of The Business Organizationsmentioning
confidence: 99%
“…Saz‐Gil et al (2020) look into how CV can result in social genuineness, and impact the health and overall wellness of employees, extending beyond their employment association, based on the sustainable development goals (SDG) as a context. Brzustewicz et al (2021) look into corporate volunteering as a philanthropic goal of organizations with their relations with NGOs. It emphasizes how CV is a key driver of value creation for the three stakeholder groups discussed.…”
Section: From the Perspective Of The Business Organizationsmentioning
confidence: 99%